A Case Series Report on the Effect of Tofacitinib on Joint Inflammation and Gut Microbiota Composition in Psoriatic Arthritis Patients Naive to Biologic Agents - Andrea Picchianti Diamanti; Concetta Panebianco; Valeria Di Gioia; Ilaria Anna Bellofatto; Simonetta Salemi; Roberta Di Rosa; Giorgio Sesti; Gabriele Nalli; Gerardo Salerno; Etta Finocchiaro; Bruno Laganà (Microorganisms)
Introduction: Psoriatic arthritis (PsA) is a complex condition within the Spondyloarthritis (SpA) group. Recent studies have focused on the important role of the intestinal microbiota in maintaining immunological homeostasis, highlighting how intestinal dysbiosis may act as a trigger for autoimmune diseases. Tofacitinib is a Janus kinase inhibitor (JAK-i) with proven efficacy for the treatment of both rheumatoid arthritis and PsA. However, there is a lack of data on its ability to reduce joint remission through ultrasonography (US) and the effects it might have on the composition of the gut microbiota. Methods: Here, we present a case series of seven bio-naïve PsA patients who received tofacitinib treatment and were followed up for 12 months. The clinical response was assessed using validated scores (DAPSA, ASDAS, and BASDAI), laboratory tests, and US assessment of the target joint and enthesis. Finally, we evaluated changes in the composition of the intestinal microbiota using next-generation sequencing analysis of fecal samples. Results: The patients in the study showed a significant improvement in all clinical scores used; this improvement was also confirmed by a significant reduction in the US synovitis scores. The data on the microbiota analysis suggested that the effectiveness of tofacitinib in ameliorating PsA activity was associated with a relevant modification of some gut bacterial lineages. No cases of severe adverse effects were reported. Conclusions: Treatment with tofacitinib proved to be effective, safe and capable of varying the composition of the gut microbiota by selecting bacterial strains considered beneficial in immune modulation.